5-(4-Fluorophenyl)-3-methylsulfanyl-2-phenyl-1-benzofuran - Uk Lee; Byeng Wha Son; Pil Ja Seo; Hong Dae Choi (Acta Crystallographica Section E, 2011)
In the title compound, C21H15FOS, the dihedral angle between the mean plane of the benzofuran fragment and the mean planes of the pendant 4-fluorobenzene and phenyl rings are 31.72 (6)° and 32.51 (6)°, respectively. In the crystal, the molecules are linked by weak C—H...π interactions. The crystal studied was a merohedral twin with a 0.62 (9):0.38 (9) domain ratio.